Program Micro Teaching Kebahasaan bagi Santri Tingkat Akhir di Pesantren Nurul Islam Aceh - Tazali, Imam; Ma'ruf, Amar; Fortuna Zulfa, Puspa (At-Tafkir, 2022)
The purpose of this study was aimed to determine the application of learning using Micro Teaching program to the final students of Nurul Islam Islamic Boarding School, Aceh. This program was conducted there. Beside, this study focused on investigating the success assessment of Micro Teaching program with the supporting factors. By applying Micro Teaching program in learning, the students are able to be active and skillful as final students in the Islamic Boarding School. This program had been conducted by concept-planning based which includes the understanding of the Micro Teaching purpose itself, especially at the Islamic Boarding School. Specifically, this program had objectives, such as for increasing the students competence in teaching and also measuring their competence in understanding material contained in each core discussion. In this study, the observation, interview and document analysis methods were carried out for collecting the data. In addition, the readability test was also conducted in accordance with the expected audio target and the end of this activity was an assessment using description of the completeness of learning during class.